The proportion of C1q-high and ISG15-high monocytes in the skin of patients with Behçet disease - Liu, Yangtengyu; Bao, Ding; Meng, Meng; Lu, Lixia; Zhu, Honglin (Frontiers in Pharmacology, 2023)
Behçet disease (BD) is a chronic systemic vasculitis that is clinically characterized by recurrent oral ulcers, genital ulcers, uveitis, and skin lesions. Here, we conducted bulk RNA-seq of skin samples from 4 BD patients and 4 normal controls (NCs). A total of 260 differentially expressed genes (DEGs), including 99 upregulated and 161 downregulated genes, were detected in the skin lesions of BD patients compared to NCs. These DEGs were mainly enriched in the following biological processes: the activation and migration of immune cells, the release of proinflammatory factors, and the IFN-γ signaling pathway. The top upregulated DEGs were CXCL10, CXCL9, FCGR3A, GBP5, GBP4, LILRB2, ADIPOQ, PLIN1, SLC43A2, and MYO1G. Using the deconvolution method CIBERSORT, we analyzed the immune cells subtypes in the skin of BD by integrating the single cell RNA-seq data from PBMC (GSE198616) and bulk RNA-seq data of skin. There was a higher proportion of C1q+ and ISG15+ monocyte subtypes in skin of BD. IHC staining of CD14 and CD16 showed that the monocyte number increased in the skin of BD. IF staining confirmed there was a higher proportion of the C1Q+Mono and ISG15+Mono subsets in the skin of BD patients. Moreover, we analyzed the average expression level of the top upregulated genes in immune cell types found in PBMC from BD patients and NCs. Almost all the top up-regulated genes expressed in monocytes. CXCL10 was specifically expressed in ISG15+monocyte, and GBP5, GBP4 and IFI44L were expressed more strongly in ISG15+ monocytes. LILRB2 was expressed more strongly in CD16+ monocytes and C1Q+ monocytes. In conclusion, our study identified that the IFN-γ pathway was activated in skin of BD and the proportion of C1q+ and ISG15+ monocyte subtype increased in the skin of BD.